1995
DOI: 10.1111/j.1365-2982.1995.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, gender, hormonal status and smoking habits on colonic transit time

Abstract: The factors that influence colonic transit time in healthy humans are not yet clearly defined. The aim of this study was therefore to determine (a) if there are differences in colonic transit time between men and women and (b) if age, female hormonal status or smoking habits are associated with alterations in these parameters. Colonic transit time was measured in 164 asymptomatic subjects (80 males, 84 females) by a radio-opaque marker technique with one single plain abdominal X-ray. Colonic transit time was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 11 publications
5
86
2
6
Order By: Relevance
“…This is perhaps in contrast to what we might expect, given that DD is an age-related phenomenon, and studies of transit time in the aged show either a slower rate of passage through the colon amongst the elderly [29][30][31] , or no differences with ageing [27,[32][33][34] . In addition, Evans et al [27] observed longer transit times in females, in whom the evidence points towards a higher risk for developing DD.…”
Section: Colonic Transit Timescontrasting
confidence: 50%
“…This is perhaps in contrast to what we might expect, given that DD is an age-related phenomenon, and studies of transit time in the aged show either a slower rate of passage through the colon amongst the elderly [29][30][31] , or no differences with ageing [27,[32][33][34] . In addition, Evans et al [27] observed longer transit times in females, in whom the evidence points towards a higher risk for developing DD.…”
Section: Colonic Transit Timescontrasting
confidence: 50%
“…Similar, but yet not statistically significant findings were found when comparing female and male patients. Surprisingly women showed better tagging results in our trial, although mean bowel transit times in female subjects are known to be higher than in male subjects (10,31). Thus, the argument of longer transit times does not seem to be conclusive for gender-related differences or there must be other factors influencing the effectiveness of fecal tagging.…”
Section: Discussioncontrasting
confidence: 65%
“…It is well established that average colonic transit times are increased in older persons (10,31). Thus, it should be considered to exceed the administration time of tagging solutions from 48 to 72 hours or even longer time ranges in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence suggests that females show more gastrointestinal symptoms than males, and there is evidence for such differences in irritable bowel syndrome (Chang et al, 2001). In healthy subjects, colonic intestinal transit times are slower in women than in men, with some data also influenced by body mass, hormonal, and smoking status (Meier et al, 1995;Graff et al, 2001).…”
Section: Discussionmentioning
confidence: 99%